Az előzetes letartóztatás néhány gyakorlati kérdése - Holhós-Kovács, Szilárd (Debreceni Jogi Műhely, 2011)
The pre-trial detention is the strictest coercive measures against a defendant in the criminal procedure. It is the most serious intervention to the private life before the final judgement. The decision of it is exclusively in the competence of courts. There are several legal reasons to issue a preliminary warrant. The pre-trial detention of the defendant may take place in a proceeding related to a criminal offence punishable by imprisonment, and only under the following conditions. a) the defendant has escaped, or has attempted to escape, or absconded from the court, the prosecutor or the investigating authority, or another procedure has been launched against the defendant for commiting a deliberate criminal offence also punishable by imprisonment, b) owing to the risk o fan escape or hiding, or for other reasons, there is reasonable cause to beleive that the presence of the defendant in procedural actions cannot be otherwise ensured, c) there is reasonable cause to beleive that if left at liberty, the defendant would frustrate, obstruct or jeopardise the evidentiary procedure, especially by means of influencing or intimidating the witnesses, or by the destruction, falsification or secretion of physical evidence or documents, d) there is reasonable cause to believe thet if left at liberty, the defendant would accomplish the attempted or planned criminal offence or commit another criminal offence punishable by imprisonment. If the conclusive decision does not become final at the time of its announcement, the court shall immediately make a decision on pre-trial detention. The pre-trial detention may also be ordered – in addition to the reasons stipulated in a), b) and d) – owing to the risk that the accused may escape or hide, taken the duration of the imprisonment imposed in the verdict. The judge has to support his or her decision with batter of statistics to establish these reasons. This essay shows the necessery examination of the legal reasons.